2015
DOI: 10.1152/japplphysiol.00054.2014
|View full text |Cite
|
Sign up to set email alerts
|

Mixed lactate and caffeine compound increases satellite cell activity and anabolic signals for muscle hypertrophy

Abstract: We examined whether a mixed lactate and caffeine compound (LC) could effectively elicit proliferation and differentiation of satellite cells or activate anabolic signals in skeletal muscles. We cultured C2C12 cells with either lactate or LC for 6 h. We found that lactate significantly increased myogenin and follistatin protein levels and phosphorylation of P70S6K while decreasing the levels of myostatin relative to the control. LC significantly increased protein levels of Pax7, MyoD, and Ki67 in addition to my… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
83
1
16

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(106 citation statements)
references
References 50 publications
6
83
1
16
Order By: Relevance
“…However, the present study did not find physical performance improvement in CG in comparison to PG differently from other studies (Chen et al, 2015; Del Coso et al, 2016). Oishi et al (2015) found that caffeine intake can actually increase muscle mass, even with low-intensity physical training due to the activation of satellite cells and of anabolic signals, fact that corroborates the results in the present study. In addition, another study found that IL-6 myokine may also control the oxidative stress condition in the skeletal muscle tissue and in immune cells (Febbraio et al, 2002).…”
Section: Discussionsupporting
confidence: 92%
“…However, the present study did not find physical performance improvement in CG in comparison to PG differently from other studies (Chen et al, 2015; Del Coso et al, 2016). Oishi et al (2015) found that caffeine intake can actually increase muscle mass, even with low-intensity physical training due to the activation of satellite cells and of anabolic signals, fact that corroborates the results in the present study. In addition, another study found that IL-6 myokine may also control the oxidative stress condition in the skeletal muscle tissue and in immune cells (Febbraio et al, 2002).…”
Section: Discussionsupporting
confidence: 92%
“…This is consistent with previous investigations reporting that protein supplementation had no effect on blood lactate concentrations [59,64]. Lactate production may contribute to mTORC1 activation [65], however the mechanisms by which metabolic stress influences anabolic signaling are not fully elucidated and warrant further investigation.…”
Section: Accepted Manuscriptsupporting
confidence: 92%
“…For example, SC reduction was found in X-linked muscular dystrophy (MDX) in mice [45] or in type 1 diabetes characterised by the alteration of Notch signalling pathway on skeletal muscle [18]. On the other hand, as observed in our study, an increase in the SC pool was described in several cases such as degenerative muscle disease [34], neuromuscular disease as "arrested development of right response" (ADR) myotonia [63], drug treatment [56], or mechanical stress [11,76]. Moreover, it is known that both number and functionality of SCs are age-dependent with a significant decline during life span until senescence [7,74].…”
Section: Mg-specific Factors Have Pathogenic Effects On the Number Ansupporting
confidence: 67%